Cefiderocol for the Treatment of Nosocomial Bloodstream Infections Caused by Stenotrophomonas maltophilia: A Case Series and Literature Review. - Vena, Antonio.; Mezzogori, Laura.; Castaldo, Nadia.; Corcione, Silvia.; Pascale, Renato.; Giannella, Maddalena.; Pinna, Simone Mornese.; Giacobbe, Daniele Roberto.; Bavaro, Davide Fiore.; Scaglione, Vincenzo.; Fumarola, Benedetta.; Pagani, Gabriele.; De Rosa, Francesco Giuseppe.; Bartoletti, Michele.; Bassetti, Matteo.; SITA GIOVANI (Young Investigators Group of the Società Italiana Terapia Antinfettiva) (Tufts University. Tisch Library., 2025)
Keywords: Stenotrophomonas maltophilia, Bloodstream infections, Multidrug resistance, Cefiderocol.; Springer Open.